2006
DOI: 10.1002/art.21620
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of early seropositive rheumatoid arthritis: Doxycycline plus methotrexate versus methotrexate alone

Abstract: Objective. To compare the efficacy of doxycycline plus methotrexate (MTX) versus MTX alone in the treatment of early seropositive rheumatoid arthritis (RA), and to attempt to differentiate the antibacterial and antimetalloproteinase effects of doxycycline.Methods. Sixty-six patients with seropositive RA of <1 year's duration who had not been previously treated with disease-modifying antirheumatic drugs were randomized to receive 100 mg of doxycycline twice daily with MTX (high-dose doxycycline group), 20 mg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 64 publications
(75 reference statements)
2
88
1
3
Order By: Relevance
“…tissue inhibitor of MMPs (TIMPs) reduces the severity of periodontitis. Also in human studies, such a possible beneficial effect of TIMPs is shown 33,34 . E.g., O'Dell et al 33 showed that systemically administration of a TIMP (subantimicrobial-dose doxycycline), FDA-approved for periodontitis, reduced the severity of RA in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…tissue inhibitor of MMPs (TIMPs) reduces the severity of periodontitis. Also in human studies, such a possible beneficial effect of TIMPs is shown 33,34 . E.g., O'Dell et al 33 showed that systemically administration of a TIMP (subantimicrobial-dose doxycycline), FDA-approved for periodontitis, reduced the severity of RA in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…This advance in effective, dose-dependent therapy was followed by the general availability of biologic therapy and the later demonstration that combinations of methotrexate and biologic agents are more effective than either treatment alone in relieving symptoms, improving function, and retarding radiographic erosion (2)(3)(4)(5)(6). Studies have also shown that simultaneous use of multiple DMARDs leads to improved outcomes (7,8), and, in some studies, treatment has resulted in profound improvement, even remission, in many users of biologic agents or combinations of biologic agents and DMARDs (2,6,9). Taken as a whole, these data imply that aggressive, high-dose, multiple-drug therapy, often including biologic agents, should be used to optimize treatment of RA.…”
mentioning
confidence: 99%
“…Certain antibiotics like tetracycline have proven eicacy in the treatment of early seropositive RA which led to the approval of minocycline, as a DMARD [22,23]. Clarithromycin is another example that gave observable beneicial efects in some refractory cases [24].…”
Section: The Infectious Hypothesis and Therapeutic Evidencesmentioning
confidence: 99%